Brief history of the hacker culture and free software - Kadrev, Vasil; Bogomilov, Ivan (Yearbook Telecommunications, 2019)
The development of computer systems and software architectures is directly related to the rise of the hacker culture, the subsequent revolution in the software industry, the GNU Project and Linux. These underlying modern concepts of free software contribute to the development of open source software products which are the bases of most modern commercial applications, Web systems, cloud infrastructure. In actual practice, the latest smart devices such as TV sets, electrical home appliances, and smart phones (running Android OS) incorporate in full or in part components with open source and Linux operating system etc. The article analyzes the stages of the emergence of hacker culture from the point of view of the emerging open source business. Summaries have been made and justification of the guidelines and development perspectives given.